Shimaji Mokurai and the reconception of religion and the secular in modern Japan - Krämer, Hans Martin (University of Hawaiʻi Press, 2015)
Categorizing religion in early modern Japan -- Early Meiji Buddhism and the Shintoist challenge -- From "sectarian teaching" to "religion" -- Western sources of knowledge -- The long history of religion's opposites: "the secular" and "secularization"